Free sialic acid levels in the cerebrospinal fluid of patients with meningitis. Issue 12 (December 1976) - Alam, T; Cherian, R; Raman, P T; Balasubramanian, A S
Abstract : The free and bound sialic acid content of cerebrospinal fluid from patients with positive evidence (by CSF culture) of pyogenic and tuberculous meningitis was determined. The free sialic acid content was significantly raised only in cases of pyogenic meningitis, but not in tuberculous or other types of the disease.